Differences in Self-Rated Health and Physical Activity due to Education Level among Koreans: Understanding Implications of Physical Education - Byung-Kweon Chang (Tehran University of Medical Sciences, 2021)
Background: We aimed to explore the effect of education levels on self-rated health and physical activity (PA) and to provide basic data for developing interventions based on physical education to improve the quality of life among Koreans.